Dog eat dog : a Melanie Travis mystery - Berenson, Laurien. frey50 (Thorndike, Me. : Center Point Pub., 2011)
Welcome to an elite Connecticut kennel club where shocking secrets gnaw at the best of the breed and competition has a sharp and deadly bite. As if raising her son Davey, training her rambunctious poodle Faith for the show ring, and grooming fellow handler Sam Driver for romance aren't enough, Melanie Travis's entree into the exclusive Belle Haven Kennel Club has been met with a grisly murder. Unfortunately, the only witnesses to the crime were the victim's startled pair of beagles. And they aren't talking. Melanie hadn't intended to do any serious snooping, what with coping with the unexpected arrival of an ex-husband out to get joint custody of the son he's never known. But she needs some distraction, so she's off to sniff out dangerous secrets, only to discover that everyone at Belle Haven has something damning to hide. As the shocking truth slowly comes to light, and her own domestic drama moves center stage, Melanie finds herself eager to put the bite on a dogged killer who's desperate enough to strike again.
Keywords: Travis, Melanie (Fictitious character); Large type books; Travis, Melanie (Fictional character); Large print books; Mystery fiction